STRATEGI KOMUNIKASI YANG EFEKTIF DALAM PROGRAM MAGANG AGRIBISNIS: MENINGKATKAN KETERLIBATAN GENERASI Z DI SEKTOR PERTANIAN - Firdauzi, Annisa; Fitriantoro, Mohamad Jatiardi; Megayana, Pramesti (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Farmer regeneration in Indonesia is an urgent problem. Various efforts and programs have been organized by the government in order to increase the interest of generation Z to be interested in the agricultural sector but have not been optimal. The government finally collaborated with universities and industry in a certified internship scheme in a modern agricultural program. The Farmhill, through the YAIP Program, has succeeded in getting more than 10,000 students to register for this program. So far, there has been no standardized internship curriculum from the government. It is important to study by analyzing the attitudes and interests of generation Z in the YAIP program and the sustainability strategy of its internship curriculum. Respondents were 90 people from the total participants of YAIP Batch 1-2. Generation Z has a positive attitude from the TRA. Clarity of the program timeline, description of program implementation, ease of access to information, participant involvement, support from field supervisors and fellow participants, and the existence of program evaluations are the most important attributes considered by Generation Z. For the government, the curriculum from the YAIP The Farmhill program can be used as a reference for developing curriculum standardization with other industries.